PENGARUH KEBIASAAN BELAJAR, LINGKUNGAN BELAJAR, DAN DUKUNGAN ORANG TUA TERHADAP PRESTASI BELAJAR MATA PELAJARAN EKONOMI PADA SISWA KELAS IX IPS DI MAN BANGKALAN - Hidayat, Mutik (UNIVERSITAS NEGERI SURABAYA, 2015)
This study aims to study the Effect of Learning Habit, Learning Environment and Support Parents on Economic Subject Learning Achievement in Class XI IPS MAN Bangkalan 2013/2014. Population was 131 students. Sample was 98 students selected by using sampling technique simple random sampling. Data were collected by questionnaires and documentation method. The method of analysis in this study was a quantitative analysis, the multiple linear regressions. The results showed that: there is a significant effect of study habits on student achievement; there was a significant effect of learning environment on student achievement; there was a significant effect of parental support on student achievement; three jointly study habits, learning environment and parental support significantly influence student achievement